Cognitive prehabilitation for geriatric patients undergoing elective surgery: a PRISMA-P-compliant protocol for a systematic review - Yu He; Nianyi Sun; Wenchen Zou; Anren Zhang; Xiaochai Han; Caitao Chen (BMJ Open)
Introduction The ageing of the population, as well as advances and improvements in surgery, and anaesthesia have greatly increased the demand for surgical services in geriatric patients. Neurocognitive disorders are the most common complications experienced in the postoperative period by older individuals. Improving perioperative brain health in older adults has become key actions for the multidisciplinary perioperative care teams. This comprehensive systematic review will assess the effectiveness and safety of cognitive prehabilitation programmes prior to surgery on cognitive functional capacity and postoperative cognitive outcomes in geriatric patients undergoing elective surgery.Methods and analysis This protocol was prepared using the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. The following key electronic bibliographic databases will be searched from inception to July 2022: MEDLINE, EMBASE, CINAHL, CENTRAL, PEDro, PsycINFO, CBM, CNKI, WANFANG database and VIP. We will include randomised controlled trials published in English or Chinese that examine the effects of cognitive prehabilitation programmes on geriatric patients undergoing elective surgery. To construct the search strategy, the Patient, Intervention, Comparison, Outcome, Study scheme will be used. Two reviewers will independently complete the study screening, selection, data extraction and quality rating. The Physiotherapy Evidence Database scale will be used to assess the methodological quality of the included studies. A narrative or quantitative synthesis will be conducted based on the final data. The planned start and end dates for the study were 1 September 2021 and 1 August 2023.Ethics and dissemination Ethical approval will not be required for this protocol. The results of the final review will be disseminated via peer-reviewed journals and conference presentations.PROSPERO registration number CRD42021277191.